Desigualdade, desequilíbrio e ajuste em sistema de previdência por repartiç\~ao - Ajax Reynaldo Bello Moreira; Sérgio Guimar\~aes Ferreira; Miguel Nathan Foguel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– In a pay-as-you-go system (SPR) receives contributions from active generations to finance the benefit of inactive people, making their financial balance depend on the proportion of inactive people in the population, a proportion that will double in Brazil in the next 30 years, making it inevitable to change the rules to mitigate the imbalance financial. In this system financial balance is achieved by increasing the contribution or reducing the benefit of agents, and these changes modify the rules of distribution, impacting agents born in the same cohort and in different cohorts differently. In this exercise, we are going to evaluate the SPR in force in Brazil in 2019/2020, where agents are heterogeneous, are inserted in a job market where there is informal employment and agents do not always contribute to social security, and there are rules that guarantee a value minimum for the benefit, and minimum income for the poor elderly. The model uses scenarios for the future evolution of productivity, the likelihood of contributing, education and demographics, to project the effect of different SPR rules on the financial results of each type of agent over the generations, and to project the financial imbalance SPR each year. To avoid the need for parametric reforms that are generally politically costly and time-consuming, we consider mechanisms for adjusting contributions and benefits that guarantee the financial balance they regulate, between active and inactive and between types of agents, the burden of canceling the imbalance.
Keywords: H55; H62; I24; 330; breakdown pension; deficit; inequality